A Stable Crown Ether Complex with a Noble‐Gas Compound. (20th August 2018) - Marczenko, Katherine M.; Mercier, Hélène P. A.; Schrobilgen, Gary J.
Abstract: Crown ethers have been known for over 50 years, but no example of a complex between a noble‐gas compound and a crown ether or another polydentate ligand had previously been reported. Xenon trioxide is shown to react with 15‐crown‐5 to form the kinetically stable (CH2 CH2 O)5 XeO3 adduct, which, in marked contrast with solid XeO3, does not detonate when mechanically shocked. The crystal structure shows that the five oxygen atoms of the crown ether are coordinated to the xenon atom of XeO3 . The gas‐phase Wiberg bond valences and indices and the empirical bond valences indicate that the Xe‐ ‐ ‐Ocrown bonds are predominantly electrostatic and are consistent with σ‐hole bonding. Mappings of the electrostatic potential (EP) onto the Hirshfeld surfaces of XeO3 and 15‐crown‐5 in (CH2 CH2 O)5 XeO3 and a detailed examination of the molecular electrostatic potential surface (MEPS) of XeO3 and (CH2 CH2 O)5 reveal regions of negative EP on the oxygen atoms of (CH2 CH2 O)5 and regions of high positive EP on the xenon atom, which are also in accordance with σ‐hole interactions.